A new method for measurement of air–fuel ratio based on the response time of binary-type exhaust gas oxygen (BEGO) sensor for application in small spark ignition (SI) engines. (April 2014) - Manivannan, PV; Singaperumal, M; Ramesh, A
A binary-type exhaust gas oxygen (BEGO) sensor that is usually used to maintain the air–fuel ratio (AFR) at stoichiometric conditions in current spark ignition (SI) engines is significantly lower in cost compared with the universal exhaust gas oxygen sensor. However, it can only switch from a high state (≈0.7 V) to a low state (≈0.1 V) when the mixture goes from richer to leaner than stoichiometric conditions or vice versa. Thus, it cannot indicate the actual AFR. A novel method of estimating the AFR of an SI engine using a BEGO sensor has been demonstrated in this work for leaner than stoichiometric mixtures. Experiments were conducted on a single-cylinder, manifold-injection SI engine. The air–fuel mixture was initially kept at a richer than stoichiometric level while the engine was maintained at constant speed and throttle. The mixture was suddenly changed to a leaner than stoichiometric level. The switching time of the BEGO sensor during this operation was noted. This was repeated for different initial and final AFRs. A relationship between the switching time and change in AFR was obtained for different initial AFRs. A look-up table to determine the AFR was made and used under test conditions. The error is less than 5% in the estimated AFR. The system was also incorporated on a low-cost microcontroller-based engine management system and tested under laboratory conditions.